A Study Based on Metabolomics, Network Pharmacology, and Experimental Verification to Explore the Mechanism of Qinbaiqingfei Concentrated Pills in the treatment of Mycoplasma Pneumonia - Liu, Zheng; Huo, Jin-hai; Dong, Wen-ting; Sun, Guo-dong; Li, Feng-jin; Zhang, Ya-nan; Qin, Zhi-wei; pengna, Jiang; Wang, Wei-ming (Frontiers in Pharmacology, 2021)
Qinbaiqingfei Concentrate Pills (QB) is a commonly used medicine for the treatment of mycoplasma pneumonia in China and its mechanism of action still needs to be further studied. Therefore, we use a combination of metabolomics and network pharmacology to clarify the mechanism of QB. Non-target metabolomics studies were performed on rat serum, urine and lung tissues, 56 therapeutic biomarkers were found. Subsequently, the components of QB absorbed into the blood and lung tissues were clarified and based on this, the core target of network pharmacology was predicted. The enrichment analysis of biomarkers-genes finally confirmed their close relationship with the NF-κB signaling pathway. By western blotting expression of the proteins in the lung tissue-related signaling pathways. It is finally confirmed that QB inhibits the NF-κB signaling pathway through SIRT1, IL-10 and MMP9, CTNNB1, EGFR and other targets. It plays a role in regulating immunity, regulating metabolism and treating diseases.